Tuberculosis in Pregnancy. Issue 6 (June 2020) - Miele, Kathryn; Bamrah Morris, Sapna; Tepper, Naomi K.
Abstract : Tuberculosis (TB) in pregnancy poses a substantial risk of morbidity to both the pregnant woman and the fetus if not diagnosed and treated in a timely manner. Assessing the risk of having Mycobacterium tuberculosis infection is essential to determining when further evaluation should occur. Obstetrician–gynecologists are in a unique position to identify individuals with infection and facilitate further evaluation and follow up as needed. A TB evaluation consists of a TB risk assessment, medical history, physical examination, and a symptom screen; a TB test should be performed if indicated by the TB evaluation. If a pregnant woman has signs or symptoms of TB or if the test result for TB infection is positive, active TB disease must be ruled out before delivery, with a chest radiograph and other diagnostics as indicated. If active TB disease is diagnosed, it should be treated; providers must decide when treatment of latent TB infection is most beneficial. Most women will not require latent TB infection treatment while pregnant, but all require close follow up and monitoring. Treatment should be coordinated with the TB control program within the respective jurisdiction and initiated based on the woman's risk factors including social history, comorbidities (particularly human immunodeficiency virus [HIV] infection), and concomitant medications. Abstract : Tuberculosis confers a high risk of maternal and fetal morbidity; screening all pregnant women and treating as appropriate is critical to reduce disease burden.